Economic and Market Value of Biogas Technology - Yousuf, Abu; Khan, Maksudur R.; Pirozzi, Domenico; Zularisam, A. W.; Atnaw, Samson M. (Springer, 2017)
The demand and prospect of biogas technology as a renewable energy source in terms of market value have not been adequately addressed. This paper focuses on the status of legal framework and future market situation related to biogas technology in order to facilitate its improvements. Biogas technology, known as biofuel production process through fermentation of biological wastes, is a well-established technique to improve lives, livelihoods, health, and ecosystem. This approach generates a large revenue opportunity that supports the socioeconomic development in rural areas. However, very little initiative has been introduced specially in the developing world to gear up the biogas technology. For more sustainable development of this technology, policy-makers should reform the existing institutional framework by reorganizing subsidies, motivating and attracting investor with flexible financial conditions, liberalizing the management of gas grids, and involving farmers in local projects. Therefore, it is a great challenge to find a proper mode of marketing policy, business models and multi-profit options, and a sustainable financing mechanism. This paper covers the state-of-the-art enlargements and future consequences of the hastily emerging biogas market, starting with a universal viewpoint and going through the market characteristics of Europe, the USA, Africa, and Asia Pacific